ANALISIS PERMAINAN TRADISIONAL DALAM PEMBELAJARAN SAINS DAN SOSIAL DI SD - Sri Wazuda, Mochamad Bagas; Nataria Wahyuning Subayani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Every region in Indonesia has traditional games that have become values in daily life as entertainment and local culture. Not only do they offer fun entertainment, but they also have great potential to support science and social learning in elementary schools. This research uses a qualitative approach research method with literature study is an approach to explore in-depth understanding of a phenomenon or issue through the analysis of relevant texts and documents. This article shows that traditional games involved in science and social learning in the classroom can overcome problems in science and social learning. This is due to the positive effects of involving traditional games in student learning in elementary school, in addition to being a fun way to deepen learning and improve learning outcomes, traditional games also train social and physical skills, and also teach cultural values and cooperation which are very beneficial in the development of student character.